THE STUDENTS’ INTEREST IN LEARNING ENGLISH: A STUDY IN THE IMPLEMENTATION OF MERDEKA CURRICULUM AT SDN 8 MAKALE - Rukmana, Haryanti; Manaya, Elzya; sirande, Normalia (Teaching English as a Foreign Language Overseas Journal, 2024)
The purpose of this study is to find out the level of interest of students in learning English in the implementation of the Merdeka Curriculum.  This study used descriptive quantitative methods. The researcher used cluster sampling to choose one of the classes of the object of study. The instruments used for data collection are observation and a questionnaire to find out students' interests. Data analysis shows that fifth grade students in SDN 8 Makale have an interest in learning English. This can be seen from the data obtained from statements 1–20, which shows that the results of the average student answer score are 81% and can be categorized on high criteria. Based on the result of the data analysis, the researcher concludes that grade V students of SDN 8 Makale have a high interest in learning English.